The relationship of individual well-being and working environment with job satisfaction among factory workers in Malaysia - A. Manaf, Aini Maznina; Tengku Mohd Azzman, Tengku Siti Aisha; Syed Abdullah Idid, Syed Arabi; Buyong, Mazni (International Islamic University Malaysia, 2019)
The present study examined the factors influencing job satisfaction in the context of factory workers in Malaysia. The major purpose of the study was to identify the main problems faced by those factory workers. The study also aimed to examine the influence of demographic variables on job satisfaction and the relationships of family income, individual well-being, and perceptions of the working environment with overall job satisfaction among those factory workers. A survey was distributed among 551 factory workers working in the Klang Valley area. Results from the survey indicated that the two main problems faced by the factory workers are, fear of the influx of foreign workers that may threaten their jobs, and the relatively low pay, taking into account the high cost of living in the Klang Valley. Findings also indicated that while gender and race did not significantly influence perceptions of the working environment and job satisfaction, job positions did. Those working as security and logistics staff were significantly more satisfied with their working environment than those holding administrative or technical/production posts. Job satisfaction also varied significantly across job positions; those working in security and logistic positions were significantly more satisfied with their jobs compared to the other employees (administrative, managerial/professional, and technical/production). Finally, using hierarchical linear regression, with family income as the control variable, the findings suggested that both individual well-being and perceptions of the working environment emerged as positive. Both of these are significant predictors of perceived job satisfaction among factory workers. The implication of these findings will be discussed within the framework of organizational satisfaction and individual well-being.*************** Kajian ini meninjau faktor-faktor yang mempengaruhi kepuasan pekerjaan di dalam konteks pekerja kilang di Malaysia. Tujuan utama kajian ini adalah untuk mengetahui pengaruh demografik ke atas kepuasan pekerjaan dan hubungan pendapatan keluarga, kesejahteraan individu, dan persepsi persekitaran pekerjaan dengan kepuasan pekerjaan di kalangan pekerja kilang. Satu kaji selidik telahdijalankan ke atas 551 pekerja kilang di sekitar Lembah Klang. Dapatan menunjukkan dua masalah utama yang dihadapi oleh pekerja kilang adalah kebanjiran pekerja asing yang mengancam keutamaan mereka dalam pekerjaan serta gaji yang rendah, megambil kira kos sara hidup yang tinggi di Lembah Klang. Dapatan juga menunjukkan bahawa jantina serta bangsa tidak mempengaruhi persepsi persekitaran pekerjaan dan kepuasan pekerjaan tetapi ainya mempengaruhi jawatan yang disandang. Pekerja dalam jawatan keselamatan dan logistik adalah lebih berpuas hati dengan pekerjaan mereka berbanding pekerja dalam jawatan lain (pentadbiran, pengurusan/professional, dan teknikal/pengeluaran). Akhir sekali, dengan menggunakan hierarchical linear rergression, dapatan mencadangkan bahawa setelah menggunakan pendapatn keluarga sebagai pengubah alih kawalan, kesejahteraan individu dan persepsi persekitaran pekerjaan dilihat sebagai positif, peramal yang signifikan terhadap kepuasan pekerjaan di kalangan pekerja kilang. Implikasi dapatan akan dibincangkandi dalam kerangka kepuasan organisasi dan kesejahteraan individu.